ANALISIS PENGARUH STORE ATMOSPHERE DAN KEDEKATAN EMOSIONAL TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI (Survei pada Pelanggan O’Pallet Cafe Boyolali) - Devi Kurnia Pertiwi; Marjam Desma Rahadhini; Retno Susanti (Universitas Slamet Riyadi, 2020)
The research was conducted at the O’Pallet Café Boyolali The purpose of this study is to analyze 1) the effect of store atmosphere on customer satisfaction; 2) the effect of emotional closeness on customer satisfaction; 3) the effect of customer satisfaction on customer loyalty; 4) the influence of store atmosphere on customer loyalty; 5) the effect of emotional closeness on customer loyalty; 6) the effect of customer satisfaction in mediating the effect of store atmosphere on customer loyalty; 7) the effect of customer satisfaction in mediating the effect of emotional closeness on customer loyalty. The type of data used is qualitative data and quantitative data, data sources consist of primary data and secondary data. The study population is all customers of O’Pallet Café Boyolali. The sampling technique used purposive sampling with slovin formula, obtained a sample size of 100 respondents. The data analysis technique used is multiple linear regression analysis and sobel tests. The result showed that store atmosphere influences customer satisfaction. Emotional closeness influences customer satisfaction. Customer satisfaction influences customer loyalty. Store atmosphere influences customer loyalty. Emotional closeness influences customer loyalty. Customer satisfaction mediates the effect of store atmosphere on customer loyalty. Customer satisfaction mediates the effect of emotional closeness on customer loyalty at O’Pallet Café Boyolali.